THE EFFECTIVENESS OF ERGONOMIC EXERCISES ON INSOMNIA LEVELS AMONG MENOPAUSAL WOMEN - Agi Yulia Ria Dini; Ela Rohaeni; Aas Hasanah (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Insomnia is a common sleep disorder among menopausal women caused by physiological and psychological changes, leading to a decline in quality of life. Preliminary findings indicate that most menopausal women in Sindangari Village experience mild to moderate insomnia. Non-pharmacological interventions such as ergonomic exercise are considered effective because they involve muscle movements and breathing techniques that promote relaxation and improve sleep quality. This study aimed to examine the effectiveness of ergonomic exercise in reducing insomnia levels among menopausal women in Sindangari Village, Sukasari District, Sumedang Regency. A pre-experimental one-group pretest–posttest design was employed. The study population consisted of 65 menopausal women with insomnia, from which 32 respondents were selected using purposive sampling. Insomnia levels were assessed using the Insomnia Rating Scale (IRS). Data were analyzed using a paired sample t-test with a significance level of 0.05. The results showed a significant reduction in insomnia levels after the ergonomic exercise intervention (p = 0.000; p 0.05). In conclusion, ergonomic exercise is effective in reducing insomnia among menopausal women and may be considered a non-pharmacological alternative to improve their quality of life.